1994
DOI: 10.1172/jci117289
|View full text |Cite
|
Sign up to set email alerts
|

Retrobulbar T cells from patients with Graves' ophthalmopathy are CD8+ and specifically recognize autologous fibroblasts.

Abstract: Graves' ophthalmopathy is an autoimmune condition characterized by T cell infiltration of the retrobulbar tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(81 citation statements)
references
References 35 publications
(32 reference statements)
2
79
0
Order By: Relevance
“…High levels of IL-2, IFN-γ, and TNF-α cytokines are secreted by Th1 cells in the retro-orbital area of patients who are diagnosed with Graves disease1617. However, another study found Th2 cell-secreted cytokines, such as IFN-γ, IL-4, and IL-10, in patients18. Moreover, a previous study described the cytokine profiles of patients diagnosed with Graves disease and thyroid disorder-associated ophthalmopathy17.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of IL-2, IFN-γ, and TNF-α cytokines are secreted by Th1 cells in the retro-orbital area of patients who are diagnosed with Graves disease1617. However, another study found Th2 cell-secreted cytokines, such as IFN-γ, IL-4, and IL-10, in patients18. Moreover, a previous study described the cytokine profiles of patients diagnosed with Graves disease and thyroid disorder-associated ophthalmopathy17.…”
Section: Discussionmentioning
confidence: 99%
“…That process, termed thyroid-associated ophthalmopathy (TAO) 3 , is connected in some as yet undefined manner with immune responses occurring in the thyroid gland. In TAO, connective tissue and extraocular muscles become infiltrated with T and B lymphocytes and mast cells (3)(4)(5). It is currently believed that these immunocompetent cells direct tissue-specific inflammatory responses and orbital fibroblast activation, culminating in hyaluronan accumulation, fibrosis, and eye motility dysfunction (6).…”
Section: Il-1␤ Induces Il-6 Expression In Human Orbital Fibroblastsmentioning
confidence: 99%
“…Eye changes result from either an autoimmune abnormality or a regulatory cell disorder that allows some antibodies to attack the ocular muscles, which leads to infl ammation and other signs of discomfort (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%